2005
DOI: 10.1002/chin.200521016
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Storage of Hydrogen in Destabilized LiBH4.

Abstract: Sorption G 6000Reversible Storage of Hydrogen in Destabilized LiBH 4 . -The addition of 0.5 equiv. MgH2 to LiBH4 yields a destabilized, reversible hydrogen storage material system with a capacity of approximately 8-10 wt% H2. MgH2 reduces the hydrogenation/dehydrogenation enthalpy by 25 kJ/(mol of H2) compared with pure LiBH4, and the temperature for an equilibrium pressure of 1 bar is estimated to be 225°C. -(VAJO*, J. J.; SKEITH, S. L.; MERTENS, F.; J. Phys. Chem. B 109 (2005) 9, 3719-3722; Hughes Res. Lab.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
129
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(143 citation statements)
references
References 1 publication
14
129
0
Order By: Relevance
“…(6) on the basis of available C p,m data for this phase [19], of selected values for the enthalpy and entropy of transition and of the thermodynamic function of the orthorhombic phase, as described above in Eqs. (8) and (9).…”
Section: Hexagonal Phasementioning
confidence: 99%
See 1 more Smart Citation
“…(6) on the basis of available C p,m data for this phase [19], of selected values for the enthalpy and entropy of transition and of the thermodynamic function of the orthorhombic phase, as described above in Eqs. (8) and (9).…”
Section: Hexagonal Phasementioning
confidence: 99%
“…Because electronic structure calculations indicate that a charge transfer from the metal cations M n þ to the [BH 4 ] anions is a key feature determining the thermodynamic stability of M(BH 4 ) n , cation and anion substitutions in LiBH 4 have been investigated [3][4][5][6][7]. Moreover, a destablization of LiBH 4 via reaction with a second hydride system has been suggested, in order to reduce the Gibbs Free Energy (GFE) difference between hydrogenated and de-hydrogenated species [2,8]. As an example, LiBH 4 -MgH 2 reactive hydride composite has been deeply studied [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the early patent from Goerrig in 1958(Goerrig, 1960 direct synthesis from gaseous H 2 was not possible for long times. Until in 2004 three different groups from the USA (Vajo et al, 2005), South Korea (Cho et al, 2006) and Germany independently discovered that by using MgB 2 instead of pure Boron as starting material formation of the respective borohydrides occurs at rather moderate conditions of 5 MPa H 2 pressure. Orimo et al (Orimo et al, 2005) reports on the rehydrogenation of previously dehydrogenated LiBH 4 at 35 MPa H 2 pressure at 600 °C.…”
Section: Borohydridesmentioning
confidence: 99%
“…The prospect of kinetic enhancement through the introduction of transition metal dopants, has led to the exploration of other materials that have favorable dehydrogenation thermodynamics but ostensibly insurmountably, slow dehydrogenation and/or re-hydrogenation kinetics. Indeed, it has recently been found that the phenomenon of kinetic enhancement upon transition metal doping extends beyond the alanates to the reversible dehydrogenation of LiNH 2 and MgH 2 /LiBH 4 (Vajo et al 2005). However, further improvement rates of dehydrogenation and re-hydrogenation remains on of the principal barriers to the practical application of these and other complex hydrides.…”
Section: Future Directionsmentioning
confidence: 99%